(untitled) (South East Asia Journal of Public Health, 2017)
The inadequate programs designed to address the numerous health problems in Nigeria have led to the little improvement in our health status. Besides the continued neglect of the importance of addressing public health issues would make matters worse for poor Nigerians most of who are at the receiving end. This study adopted a qualitative approach, so as to adequately describe the study aims and objectives. The data for this study were collected through scientific database sources, web search engines, direct observation and relevant documents from the Nigerian Ministry of Health. The major public health challenges Nigeria faces are infectious diseases, control of vector some diseases, maternal mortality, infant mortality, poor sanitation and hygiene, disease surveillance, non-communicable diseases and road traffic injuries etcetera. Nigeria is currently working towards achieving the Millennium Development Goals. Despite the collaborative efforts of both Nigerian Government, Donor Agencies and NGOs to provide an efficient and effective health care delivery in Nigeria. South East Asia Journal of Public Health Vol.7(1) 2017: 6-11